Two distinct and frequently mutated regions of retinoblastoma protein are required for binding to SV40 T antigen. - Huang, S (1990)
The retinoblastoma susceptibility gene (RB) encodes a phosphoprotein of 110 kd (pp110RB) that forms specific complexes with SV40 T antigen and the transforming proteins of several other DNA tumor viruses. Interaction with RB is thought to contribute to transformation by these viruses as demonstrated by genetic analyses. To help understand the function of these interactions, the regions of RB that are involved in binding to T have been mapped. An in vitro protein synthesis system capable of producing full-length RB protein has been developed to facilitate the mapping study. A 5- to 10-fold increase in translational efficiency in the reticulocyte lysate was obtained when the 5' non-coding region of RB mRNA was replaced with that of beta-globin mRNA or a plant viral RNA, alfalfa mosaic virus (AMV) RNA4. A series of mutated RB polypeptides produced from this system were assayed for T binding. Two non-contiguous regions of the RB protein, amino acid residues 394-571 and 649-773, were found to be necessary for binding to T: mutations in either region abolished T-RB complex formation. These results are consistent with the finding that, in all the cases analyzed so far, mutated RB proteins in human tumor cells also failed to bind to T antigen due to deletions including at least one of the two required regions. Thus the regions of RB defined in vitro as necessary for interaction with T might be physiologically relevant as well, and might play a fundamental role in normal RB protein function.